An ecological study of food desert prevalence and 4th grade academic achievement in New York State school districts - Seth E. Frndak (Journal of Public Health Research, 2014)
Background. This ecological study examines the relationship between food desert prevalence and academic achievement at the school district level. Design and methods. Sample included 232 suburban and urban school districts in New York State. Multiple open-source databases were merged to obtain: 4th grade science, English and math scores, school district demographic composition (NYS Report Card), regional socioeconomic indicators (American Community Survey), school district quality (US Common Core of Data), and food desert data (USDA Food Desert Atlas). Multiple regression models assessed the percentage of variation in achievement scores explained by food desert variables, after controlling for additional predictors. Results. The proportion of individuals living in food deserts significantly explained 4th grade achievement scores, after accounting for additional predictors. School districts with higher proportions of individuals living in food desert regions demonstrated lower 4th grade achievement across science, English and math. Conclusions. Food deserts appear to be related to academic achievement at the school district level among urban and suburban regions. Further research is needed to better understand how food access is associated with academic achievement at the individual level.